Quantitative analysis of the impacts of climate and land-cover changes on urban flood runoffs: a case of Dar es Salaam, Tanzania - Philip Mzava (IWA Publishing, 2021)
Over the past half-century, the risk of urban flooding in Dar es Salaam has increased due to changes in land cover coupled with climatic changes. This paper aimed to quantify the impacts of climate and land-cover changes on the magnitudes and frequencies of flood runoffs in urban Dar es Salaam, Tanzania. A calibrated and validated SWAT rainfall-runoff model was used to generate flood hydrographs for the period 1969–2050 using historical rainfall data and projected rainfall based on the CORDEX-Africa regional climate model. Results showed that climate change has a greater impact on change in peak flows than land-cover change when the two are treated separately in theory. It was observed that, in the past, the probability of occurrence of urban flooding in the study area was likely to be increased up to 1.5-fold by climate change relative to land-cover change. In the future, this figure is estimated to decrease to 1.1-fold. The coupled effects of climate and land-cover changes cause a much bigger impact on change in peak flows than any separate scenario; this scenario represents the actual scenario on the ground. From the combined effects of climate and land-cover changes, the magnitudes of mean peak flows were determined to increase between 34.4 and 58.6% in the future relative to the past. However, the change in peak flows from combined effects of climate and land-cover changes will decrease by 36.3% in the future relative to the past; owing to the lesser variations in climate and land-cover changes in the future compared with those of the past. HIGHLIGHTS Investigate temporal variability of urban flood runoffs from the impacts of climate and land-cover changes.; Compare past and future peak flow trend magnitudes based on CORDEX-Africa RCM under RCP4.5.; Investigate changes in the historical and future intensities of urban flood runoffs.; Illustrate the probabilistic impacts of climate and land-cover changes on the recurrence intervals of urban floods.;